Physical Drivers and Stranded Assets in Agriculture: The Case of Honduras - Ardon M., Allan R. (Zamorano: Escuela Agrícola Panamericana, 2023)
Stranded assets are those that do not generate expected returns and have become a growing concern in agriculture due to environmental related risks. Honduras is a developing country extremely vulnerable to climatic phenomena which makes agriculture face challenges that threaten its profitability. This study aims to gather information on the physical factors associated with climate change and its economic impact on Honduran agriculture. Some of the physical factors mentioned in this study are climate variability and water scarcity, soil degradation, loss of biodiversity and ecosystem services, and phosphate availability in the middle and long term. To address these challenges, it is crucial to take urgent measures to promote sustainable agricultural practices. Collaboration between universities, businesses and governments plays a key role in mitigating the effects of climate change and achieving a successful transition to a more resilient and sustainable agriculture. Through the implementation of adaptive strategies, research, and innovation, it is possible to overcome the current and future challenges of Honduran agriculture, ensuring the sustainable development of the country.